2019
DOI: 10.3390/en12030353
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of a Spectrum Splitter of TechSpec AOI 50.0mm Square Hot and Cold Mirrors Using a Halogen Light for a Photovoltaic-Thermoelectric Generator Hybrid

Abstract: The characterization of a spectrum splitter of both hot and cold mirror, type TechSpec AOI 50.0, using a 50-Watt halogen bulb light has been done. Both the bulb spectrum, prior to and after spectrum splitting, are described in this study to see the degradation of radiation that occurs because partial energy is absorbed by the splitter. This characterization plays an important role in determining the best position of a photovoltaic (PV) and thermoelectric generator (TEG) in a PV-TEG system. The light spectrum w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…Pada penelitian ini manfaat cahaya malam berfungsi ganda sebagai sumber energi baru pembangkit energi listrik (PLTBoh). Piarah et al, [4] dan [5] telah megeoksplorasi lebih jauh studi yang dilakukan oleh [6] dalam bentuk eksperimen penggunaan bohlam jenis Xenon, pijar dan Halogen sebagai sumber energi foton untuk modul mini PV. Namun, jenis bohlam ini tidak komersil sehingga masih terbatas aplikasinya di masyarakat umum.…”
Section: Pendahulanunclassified
“…Pada penelitian ini manfaat cahaya malam berfungsi ganda sebagai sumber energi baru pembangkit energi listrik (PLTBoh). Piarah et al, [4] dan [5] telah megeoksplorasi lebih jauh studi yang dilakukan oleh [6] dalam bentuk eksperimen penggunaan bohlam jenis Xenon, pijar dan Halogen sebagai sumber energi foton untuk modul mini PV. Namun, jenis bohlam ini tidak komersil sehingga masih terbatas aplikasinya di masyarakat umum.…”
Section: Pendahulanunclassified
“…An interesting result is described in the paper; namely, during the night, there was a temperature difference between the PV and the ambient temperature (the cold side of the TEG), which resulted in electrical generation during the entire night. Piarah et al [52] characterized a spectrum splitter for an indirectly coupled PV-TEG HS. They considered two spectrum splitters, the first with a hot mirror and the second with a cold mirror, and analyzed the right positioning of both the PV and TEG modules relative to the transmitted or reflected radiance.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Furthermore, the PV cell and TE module's power generation had opposite trends with change in the figure of merit. In order to determine the best location of the TE module and PV cell in a TE-PV -BS system, Piarah et al [23] characterized both cold and hot mirrors, type TechSpec AOI 50.0, as the spectrum splitter in the system. It was indicated that when a cold mirror is utilized as the spectrum splitter, the maximum power generation can be 40% higher than when a hot mirror is used in the system.…”
Section: Introductionmentioning
confidence: 99%